Efficient Inhibition of Streptococcus agalactiae by AIEgen-Based Fluorescent Nanomaterials - Yi, Mengmeng; Wang, He; Wang, Miao; Cao, Jianmeng; Gao, Fengying; Ke, Xiaoli; Liu, Zhigang; Liu, Ying; Lu, Maixin (Frontiers in Chemistry, 2021)
Streptococcus agalactiae, referred to as group B streptococcus (GBS), is a prominent co-pathogenic bacterium causing the onset and death of human, animal, and aquatic products. Although antibiotics are efficient against GBS, antibiotic resistance through antibiotic overuse is an equally serious problem. Therefore, the treatment of GBS infection appears strongly dependent on nonantibiotic therapy, such as photodynamic therapy. Different from other photosensitizers (PSs), luminogens with aggregation-induced emission (AIEgen) can efficiently generate fluorescence and reactive oxygen species (ROS). Herein, TBP-1, an efficient AIE PSs, is chosen to resist GBS, and its antibacterial activity and the killing mechanism toward GBS are investigated. The ROS generation performance and the images of GBS treated with TBP-1 in the dark or under white light irradiation were investigated. TBP-1 with its high ROS generation ability can efficiently kill GBS and serve as a novel treatment strategy against GBS infection.